Dynamic Regulation of the Adenosine Kinase Gene during Early Postnatal Brain Development and Maturation - Kiese, Katharina; Jablonski, Janos; Boison, Detlev; Kobow, Katja (Frontiers in Molecular Neuroscience, 2016)
The ubiquitous metabolic intermediary and nucleoside adenosine is a “master regulator” in all living systems. Under baseline conditions adenosine kinase (ADK) is the primary enzyme for the metabolic clearance of adenosine. By regulating the availability of adenosine, ADK is a critical upstream regulator of complex homeostatic and metabolic networks. Not surprisingly, ADK dysfunction is involved in several pathologies, including diabetes, epilepsy, and cancer. ADK protein exists in the two isoforms nuclear ADK-L, and cytoplasmic ADK-S, which are subject to dynamic expression changes during brain development and in response to brain injury; however, gene expression changes of the Adk gene as well as regulatory mechanisms that direct the cell-type and isoform specific expression of ADK have never been investigated. Here we analyzed potential gene regulatory mechanisms that may influence Adk expression including DNA promoter methylation, histone modifications and transcription factor binding. Our data suggest binding of transcription factor SP1 to the Adk promoter influences the regulation of Adk expression.